Aseptic meningitis after posterior fossa surgery treated by pseudomeningocele closure. Issue 2 (1st February 2000) - Hillier, C E M; Stevens, A Penrose; Thomas, F; Vafidis, J; Hatfield, R
Abstract : Aseptic meningitis is a recognised complication after posterior fossa surgery. It is often self limiting but occasionally runs a protracted course requiring repeated CSF examination to exclude infection, and treatment with systemic steroids. A patient is described with aseptic meningitis after posterior fossa surgery who underwent posterior fossa re-exploration nearly 3 years after the initial operation. This disclosed a pseudomeningocele, which was closed. The patient remains symptom free almost 2 years after closure. In this case of chronic aseptic meningitis after posterior fossa surgery, closure of the pseudomeningocele found at exploratory surgery led to resolution of the symptoms.